Gambaran Tingkat Persepsi Risiko Pekerja Sektor Pertambangan Batubara PT Y - Irsyad Asyrafil Firdaus; Endang Dwiyanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Risk perception is a crucial element in occupational health and safety, particularly in high-risk environments such as mining. Workers with a better understanding of the risks in the workplace tend to be more cautious. Therefore, it is essential to comprehend how workers assess the risks they face and how this perception influences their behavior. This study aims to identify the risk perception levels of workers at PT Y in South Kalimantan, specifically in the context of occupational health and safety within the mining environment. Utilizing a descriptive quantitative approach and simple random sampling technique, the study involves 324 randomly selected respondents from the operational division. The results indicate that workers' risk perception tends to increase with age, with older age groups having a higher risk perception. The dimension of risk perception with the highest score is the Immediacy of Effect, which reflects workers' attention to risks with immediate consequences, such as work-related accidents. Conversely, the Chronic-Catastrophic dimension shows a low score, indicating a lack of attention to long-term risks. This study recommends that the company implement training based on visual simulations using the SMART approach to enhance workers' awareness of risks and strengthen the risk perception at PT Y.